The impact of high-dose chemotherapy, autologous stem cell transplant and conventional chemotherapy on quality of life of long-term survivors with follicular lymphoma - Andresen, Silke; Brandt, Juliane; Dietrich, Sascha; Memmer, Marie-Luise; Ho, Anthony Dick; Witzens-Harig, Mathias (Leukemia and lymphoma, 2012)
In this study we investigated the quality of life (QoL) of long-term survivors with follicular lymphoma (FL) after high-dose chemotherapy (HDCT) and autologous stem cell transplant (ASCT) using two standardized questionnaires. Altogether, 124 patients with FL were included in the study. A total of 63 patients received HDCT with ASCT, and this group was compared with 61 patients who were treated with rituximab and CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) chemotherapy and supplementary radiation. In addition, the QoL of the patients was compared to the QoL of healthy people on the basis of two studies about the general health status of the German population. When the QoLs of the HDCT group and the conventional therapy group were compared, there was a tendency for better QoL in the HDCT group, maybe due to a higher proportion of patients in complete remission (CR) or a longer follow-up period in the HDCT group (8.5 years vs. 4.5 years in the conventional therapy group). In both the HDCT group and the conventional therapy group, the results of the questionnaires showed a reduced QoL compared to the healthy population. In this study, there was a tendency for better QoL in the HDCT group compared to the conventional therapy group. However, the negative impact of both HDCT and conventional therapy on the QoL of patients with follicular lymphoma should not be underestimated and should lead to the development of less toxic therapy strategies.
Published online 10 October 2011
Gesehen am 11.06.2018